EFFICACY OF Paecilomyces lilacinus ISOLATES FOR THE CONTROL OF ROOT-KNOT NEMATODE (Meloidogyne incognita [Kofoid and White] Chitwood) IN SWEETPOTATO - Galano, C.D.; Gapasin, R.M.; Lim, J.L. (Annals of Tropical Research, 1996)
The application of different Paecilomyces lilacinus isolates grown in water hyacinth substrate, 50 days after Meloidogyne incognita egg inoculation increased fresh vine and fibrous root weights by 32.6-36.2% and 29.6-35.1%, respectively over the untreated control. On the other hand, chicken manure and ethoprop (Mocap)-treated plants had an increase of 37.9-43.0% and 18.6-29.9%, respectively. The mean number of root galls, egg masses produced and nematode population in fibrous roots and soil in plants applied with P. lilacinus isolates ranged from 27.8-42.0, 40.9-58.1, 8.4-11.5 and 392.0-800.8, respectively. The isolates evaluated for their efficacy gave comparable effects since no significant differences in effect were observed among them. Chicken manure-treated plants had a mean number of root galls of 28.8 and egg masses of 40.3 showing an egg mass reduction of 55.7%. Ethoprop gave the lowest number of galls (4.2) and egg masses (6.2) among the treatments. Percent reduction based on egg masses produced was 93.2 relative to the untreated control. The overall results of the study showed that the efficacy of P. lilacinus in reducing root-knot galls, egg masses and nematode population was comparable to chicken manure but not with ethoprop.